# Have-t Sentence Examples

At the vertex A, where y =H, we

**have t**= t' =1-T, so that (33) H = sgT2, which for practical purposes, taking g= 32, is replaced by (34) H = 4T 2, or (2T)2.If a i, a 2 represent the densities of the two infinite solids, their mutual attraction at distance z is per unit of area 21ra l a fZ '(z)dz, (30) or 27ra l 02 0(z), if we write f 4,(z)dz=0(z) (31) The work required to produce the separation in question is thus 2 7ru l a o 0 (z)dz; (32) and for the tension of a liquid of density a we

**have T**= a f o 0 (z)dz.If v= X/r we

**have T**= PX3 2 coth 27rh gX 2 p .Whilst I have done this on a smaller, local/regional level I havent yet approached the major corporates.

Advertisement